A Survey of Default Risk Methodologies for Equity Pricing with a Focus on Advances in the Field of Default Risk Assessment and Equity Pricing in Pakistan - Ahmed, Jamil; khilji, Dr Jameel A (The journal of contemporary issues in business and government, 2021)
The aim of this study is to review the default risk modelling literature from the perspective of Pakistan, where an effort has been put to cover the three classes of such models i.e. Accounting, Structural and Logit based hazard models. As per review it is very clear that the first two modelling techniques are extensively employed in Pakistan with Z-Score and KMV Merton model as commonly used estimation technique. Hazard models are the least used due to data issues, as for majority of delisted firms’ data is not available in data services like Thomson Reuters Eikon and Bloomberg before 2000 and even local data sources like Pakistan Stock Exchange is not of much help. Due to the reason Hazard Models are least employed for default risk estimation in Pakistan along with neural network models being most neglected one with only one paper in 2020. The review helps in identifying the gaps in this area of study, which include identification of models for future research and data issues in Pakistan along with equity pricing implications.